Global boundedness of a class of multilinear Fourier integral operators. (22nd February 2021) - Rodríguez-López, Salvador; Rule, David; Staubach, Wolfgang
Abstract: We establish the global regularity of multilinear Fourier integral operators that are associated to nonlinear wave equations on products of $L^p$ spaces by proving endpoint boundedness on suitable product spaces containing combinations of the local Hardy space, the local BMO and the $L^2$ spaces.